PENGARUH KEPUASAN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA BALAI BESAR METEOROLOGI KLIMATOLOGI DAN GEOFISIKA WILAYAH II TANGERANG SELATAN - Yandani, Kandi; Andi, Dede (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of job satisfaction and motivation on employee performance at the Center for Meteorology, Climatology and Geophysics Region II, South Tangerang, both partially and simultaneously. The research method used is a quantitative descriptive method. The population in this study was 80 employees with the sampling technique used was saturated samples (census) so that respondents were obtained as many as 80 employees. Meanwhile, the primary data collection technique is through a questionnaire which is processed using the SPSS Version 26 application system. The data analysis methods used in this research are correlation analysis, regression analysis, determination analysis, t test and f test. Based on the results of the t test research, tcount for job satisfaction was tcount 5.192 > ttable 1.665. or significance 0.000 < 0.05, meaning that partially there is a significant influence of job satisfaction on employee performance. And tcount motivation is tcount 5.061 > t table 1.665. or significance 0.000 <0.05, meaning that partially there is a significant influence of motivation on employee performance. For the f test, Fcount is 19.762 > Ftable 3.115. or significance 0.000 < 0.05, meaning that simultaneously there is a significant influence of job satisfaction and motivation on employee performance. Multiple linear regression analysis obtained the equation Y = 14.108 + 0.315 (X1) + 0.321 (X2). Determination analysis obtained a value of 0.339 with a percentage of 33.9%, while the remaining 66.1% was influenced by other variables.